Exploring the Combined Effects of Rater Misfit and Differential Rater Functioning in Performance Assessments. (October 2019) - Wind, Stefanie A.; Guo, Wenjing
Rater effects, or raters' tendencies to assign ratings to performances that are different from the ratings that the performances warranted, are well documented in rater-mediated assessments across a variety of disciplines. In many real-data studies of rater effects, researchers have reported that raters exhibit more than one effect, such as a combination of misfit and systematic biases related to student subgroups (i.e., differential rater functioning [DRF]). However, researchers who conduct simulation studies of rater effects usually focus on the effects in isolation. The purpose of this study was to explore the degree to which rater effect indicators are sensitive to rater effects when raters exhibit more than one type of effect, and to explore the degree to which this sensitivity changes under different data collection designs. We used a simulation study to explore combinations of DRF and rater misfit. Overall, our findings suggested that it is possible to use common numeric and graphical indicators of DRF and rater misfit when raters exhibit both these effects, but that these effects may be difficult to distinguish using only numeric indicators. We also observed that combinations of rater effects are easier to identify when complete rating designs are used. We discuss implications of our findings as they result to research and practice.